Probiotic Lactobacilli ameliorate alcohol-induced hepatic damage via gut microbial alteration - Kim, Juseok; Ahn, Seong Woo; Kim, Joon Yong; Whon, Tae Woong; Lim, Seul Ki; Ryu, Byung Hee; Han, Nam Soo; Choi, Hak-Jong; Roh, Seong Woon; Lee, Se Hee (Frontiers in Microbiology, 2022)
Alcoholic liver disease (ALD), which includes fatty liver, cirrhosis, steatosis, fibrosis, and hepatocellular carcinoma, is a global health problem. The probiotic effects of lactic acid bacteria (LAB) are well-known; however, their protective effect against ALD remains unclear. Therefore, in this study, our objective was to assess the protective effects of LAB on ALD. To this end, mice were fed either a normal diet or an alcohol diet for 10 days (to induce ALD) accompanied by vehicle treatment (the NC and AC groups) or kimchi-derived LAB (Lactiplantibacillus plantarum DSR J266 and Levilactobacillus brevis DSR J301, the AL group; or Lacticaseibacillus rhamnosus GG, the AG group). Our results showed that mice in the AC group showed significantly higher serum aspartate aminotransferase and alanine aminotransferase levels than those in the normal diet groups; however, their levels in the AL and AG groups were relatively lower. We also observed that the AL and AG groups showed relatively lower interleukin-6 levels than the AC group. Additionally, AC group showed the accumulation of several fat vesicles in the liver, while the AL and AG groups showed remarkably lower numbers of fat vesicles. The relative abundance of Enterococcus feacalis, which showed association with liver injury, significantly increased in the AC group compared with its levels in the normal diet groups. However, the AG group showed a decreased relative abundance in this regard, confirming that LAB exerted an improvement effect on gut microbial community. These findings suggested that via gut microbiota alteration, the ingestion of LAB can alleviate the ill effects of alcohol consumption, including inflammation, liver damage, gut dysbiosis, and abnormal intestinal nutrient metabolism.